Restorative Model: the Alternative Justice Response to the Victims of Sexual Violence - Mohamad Ismail Bin Mohamad Yunus (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
It is seen there is no proper repositioning of the victims of sexual crimes since the process of contrarian justice is only concerning the sexual offender. Alternative justice models for victims of sexual crimes by involving them in the judiciary process result is necessary to do. However, there is a command from the court for an offender in indemnification though recompensing judgment by Criminal Procedure Code is legitimated. Examining compensation for the victim and urging a legitimated system as alternative justice models for sexual criminal crimes are the aims of this study. The legitimated system as alternative justice which will be recommended in this article is mechanism suitable for justice administration in Malaysia. Through recompensing as well as indemnification, it is considered as a model that can make an impact in restorative justice as the response of alternative justice. Victim Compensation Scheme (VCS) is aimed to be formed and applied with the control of the Criminal Procedure Code too. Keywords: Response of Alternative Justice, Sexual Force Victims